#lagentilezzaticontagia. Sperimentazioni antropologiche e public engagement tra formazione, ricerca-azione e sviluppo territoriale - Brambilla, Chiara (Antropologia Pubblica, 2024)
This paper will focus on a participatory action research project, #lagentilezzaticontagia that was promoted by the Volunteer Work Centre of Bergamo (CSV) in partnership with the Department of Human and Social Sciences at the University of Bergamo. The project was carried out in 4 territorial-administrative units (ambiti) of the Province of Bergamo starting from the early stage of the Covid-19 pandemic in spring 2020, with the aim of creating a space of reflection on relevant transformations in solidarity practices and social ties produced by the pandemic within local communities. The project will be analyzed as a case in which the anthropological approach has acted as a driving force for applying the Third Mission with a view to transformation, encouraging a fruitful interchange between training, action research and local development. We will see how innovative elements of the project can be regarded as useful tools for realizing the union between university research and public engagement in a Third Mission understood not only as a way for valorizing the insights of higher education and bringing them to the public sphere, but also for generating community sustainable development with an approach of transformative resilience. At the same time, we will explore problem areas of the project and obstacles in achieving Third Mission’s goals, also considering difficulties in adopting an anthropological approach. The paper concludes by reflecting on the Third Mission as a “creative challenge” not only to enhance the role of anthropological knowledge and practices in public space, but also to rethink